Effect of Dietary Inclusion of a Plant Extract Blend on Broiler Growth Performance, Nutrient Digestibility, Caecal Microflora and Intestinal Histomorphology - Attia, G.; El-Eraky, W.; Hassanein, E.; El-Gamal, M.; Farahat , M.; Hernandez-Santan, A. (International Journal of Poultry Science, 2017)
Objective: This trial was conducted to determine if the growth performance, apparent nutrient digestibility, caecal microflora and intestinal histomorphology of broiler chickens could be enhanced via supplementation of their diets with a blend of plant extracts containing oregano, fenugreek, chamomile and fennel. Methodology: The plant extract blend was included as a natural growth promoter in six dietary treatments at levels of 0, 100, 200, 500, 1000 and 2000 ppm. A seventh treatment, supplemented with 200 ppm oxytetracycline (OTC) antibiotic as growth promoter, was included in the study design to compare its effect to those fed on the plant extract blend (0 and 200 ppm). The trial utilized 245, day-old chicks distributed in 7 dietary treatments (7 birds/pen; 5 replicate pens/treatment). Results: No significant differences were observed in the measured growth performance parameters (body weight, daily gain, daily feed intake and feed conversion ratio) due to inclusion of the plant extract blend (p>0.05). Supplementation of the broiler diet with 200 ppm of OTC resulted in significant improvement in the measured growth performance parameters compared to those fed on 0 (control) or 200 ppm of the plant extract blend. The mortality percentage in the control group was 11.4% and was decreased by an average of 50-75% in broilers fed on the plant extract blend. No mortality was observed in broilers fed on the 200 ppm OTC. The apparent total tract digestibility of dry matter, crude protein and ether extract was increased due to inclusion of the plant extract blend or OTC. The caecal microflora count was positively influenced (p